Rebels with a Cause? Supporting Library and Academic-led Open Access Publishing - Deville, Joe; Sondervan, Jeroen; Stone, Graham; Wennström, Sofie (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2019)
The authors, who all have experience with academic publishing, outline the landscape of new university and academic-led open access publishing, before discussing four interrelated sets of challenges which are often referred when questioning the viability of such publishing ventures. They are: (1) professionalism, (2) scale, (3) quality, and (4) discoverability & dissemination. The authors provide examples of how, albeit differing in size, form and ambition, these new presses are not just adhering to conventional publishing norms but often innovating in order to surpass them.